Cloud Computing as an Alternative IT Solution for SMEs: A System Dynamic Approach - Abdillah, Mochamad Arief (School of Business and Management Institut Teknologi Bandung, 2014)
Small medium enterprises (SMEs) play a big role for GDP in Indonesia. In 2012, SMEs made contribution 59,08 % for GDP Indonesia. The amount of SMEs in Indonesia is 99,99 % from total company in Indonesia. From that data, we know that SMEs is very big market in Indonesia. However, despite many big contributions that SMEs gave, SMEs also have challenges for themselves. The limitation of capital is one of challenges that SMEs have to face. The limit of capital make SMEs spend their capital wisely. They have to think very carefully how to expand their business. Is it profitable or not. In this paper we want to understand about the phenomenon why SMEs are hard to implement information and system technology. We used observation and secondary data to construct the variables. After that, we use the variables to build the model using system dynamics. And then we simulate it to know the impact implementation of information technology to flow business of SMEs. To propose new alternative technology (cloud computing), we modified the variables in the model and simulated it. We compared the result between own information technology and cloud computing. The result shows that cloud computing is suitable to be implemented in SMEs.Keywords : Cloud computing, SME, System Dynamic, Information Technology, Model